Marine Transgression, Aboriginal Narratives and the Creation of Yorke Peninsula/Guuranda, South Australia. (2nd July 2020) - Roberts, Amy L.; Mollenmans, Adrian; Rigney, Lester-Irabinna; Bailey, Geoff
Abstract: This paper provides new palaeogeographical reconstructions of the Spencer Gulf and Yorke Peninsula/Guuranda region of South Australia for the period ca. 20, 000–6000 cal. BP. The rich complexity of traditional Aboriginal (Narungga) sea-level narratives is also explored. These narratives, which form a highly significant system of knowledge, are considered together by the Narungga and non-Narungga authors of the paper to generate a new dialogue about Aboriginal traditions and scientific data. The dialogue between the Narungga knowledge systems and palaeogeographic mapping reveals a strong concordance for events/time slices inclusive of the onset of marine transgression, the creation of northern Spencer Gulf and the formation of some islands—while also establishing that there are deeper complexities inherent within Narungga narratives that demonstrate layers of meaning at multiple scales. The palaeogeographic reconstructions are also considered in relation to the known archaeology and geomorphology of the region as well as new observations arising from this research. Targets for future underwater (and terrestrial) investigation relating to the periods of marine transgression are also outlined.